Stability of the conservative mode of nucleosome assembly. - Leffak, I M (1983)
The conservative assembly of nucleosome histone octamer cores has been confirmed by electrophoretic analysis of density labeled histones following equilibrium buoyant density centrifugation. After normal replication, crosslinked octamers are shown not to contain a mixture of new and old core histones. Moreover, when DNA synthesis is inhibited by ara-C nucleosome cores are still assembled exclusively from nascent histone. Similarly, after release from cycloheximide inhibition newly synthesized core histone is conservatively deposited. Thus, a conservative mechanism of histone octamer assembly occurs when nascent histone is present in the normal stoichiometry to nascent DNA and when chromatin is assembled in nascent histone or nascent DNA excess.